Non-destructive analyses of bronze artefacts from Bronze Age Hungary using neutron-based methods. Issue 3 (9th January 2015) - Kiss, V.; Fischl, K. P.; Horváth, E.; Káli, Gy.; Kasztovszky, Zs.; Kis, Z.; Maróti, B.; Szabó, G.
Abstract : Our paper produces results on production techniques of prehistoric metal artefacts using non-destructive neutron-based methods, considering aspects of heritage protection. Abstract : In this paper we present the application of various neutron-based methods carried out at the Budapest Neutron Centre. Non-destructive and non-invasive neutron radiography (NR), prompt gamma activation analysis (PGAA) and time-of-flight neutron diffraction (TOF-ND) analysis were applied to reveal more information on raw material and production techniques of bronze artefacts that can be dated to the Central European Bronze Age (2000–1200 BC).